Empowerment of Gender-Based Small-Scale Fishers to Strengthen the Coastal Economy: Case Study Batang Regency - Arisanti Ayu Wardhani; Indah Susilowati; Nugroho SBM (Jurnal Ilmu Sosial dan Humaniora, 2023)
This study aims to analyze gender roles in fishing households and formulate gender-based fishers empowerment strategies. This research focuses on the Coastal Area of Batang Regency, Central Java Province, Indonesia. The approach used in this study is a mixed method using two approaches: qualitative and quantitative. The approach used in this study is a mixed method with a quantitative approach using descriptive statistics and a qualitative approach using Atlas Ti. Using snowballing sampling, data were obtained through in-depth interviews and questionnaires with selected fishing communities. The results showed that the distribution of gender roles in fishing households is still unbalanced, where women as wives have roles that focus more on reproductive aspects such as taking care of the household and children. While many aspects of production are dominated by men, in addition to aspects of society, both women and men have a balanced role. To encourage gender-based fishers' empowerment, it is necessary to increase the role of women in the production aspect, where the provision of entrepreneurship-related training is essential. In addition, the women's side should encourage the establishment of small and medium enterprises to promote the economic well-being of the family. The findings show that gender-based empowerment in coastal areas is needed to strengthen the economy of small-scale fishermen. Moreover, women have an essential role in maintaining the stability of their families.